2005
DOI: 10.1093/geronb/60.4.p182
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Complaints, Subjective and Objective Sleep Patterns, Health, Psychological Adjustment, and Daytime Functioning in Community-Dwelling Older Adults

Abstract: We examined sleep complaints, subjective and objective sleep patterns, health, psychological adjustment, and daytime functioning in 103 community-dwelling older adults to identify factors associated with sleep complaints. We collected 2 weeks of sleep diaries and actigraphy. Only health distinguished complaining from noncomplaining sleepers. Noncomplaining good sleepers had poorer objective sleep quantity than complaining poor sleepers. Actigraphy distinguished noncomplaining good and complaining poor sleepers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
107
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(124 citation statements)
references
References 17 publications
9
107
6
Order By: Relevance
“…In other words, in aSAH patients, long S4 sleep might rather be an indication of chronic fatigue than of restoring sleep, although the absence of a measure of chronic fatigue in this study means that this observation cannot be confirmed for the present sample. While findings regarding the correlation of subjective and objective sleep are mixed [79], in their summary of research on poor sleep in later life, McCrae et al [80] emphasise that although the quality of subjective and objective sleep does not always correlate, sleep satisfaction, rather than the objectively measured quality of sleep, plays a greater role in well-being, a finding our data supports.…”
Section: Discussionsupporting
confidence: 70%
“…In other words, in aSAH patients, long S4 sleep might rather be an indication of chronic fatigue than of restoring sleep, although the absence of a measure of chronic fatigue in this study means that this observation cannot be confirmed for the present sample. While findings regarding the correlation of subjective and objective sleep are mixed [79], in their summary of research on poor sleep in later life, McCrae et al [80] emphasise that although the quality of subjective and objective sleep does not always correlate, sleep satisfaction, rather than the objectively measured quality of sleep, plays a greater role in well-being, a finding our data supports.…”
Section: Discussionsupporting
confidence: 70%
“…4,5 Consistent with this, our overall sample reported poor sleep quality, which included two hallmarks of insomnia: difficulty initiating and/or maintaining sleep. In addition, African Americans had poorer sleep quality than Whites, as previously demonstrated.…”
Section: Discussionsupporting
confidence: 68%
“…1,2,3 The hallmark sleep complaint in old age is insomnia, with prevalence rates ranging from 15%-65%. 4,5 Empirical studies support that aging is associated with shorter sleep times, decreased time in deep sleep, increased arousals, and diminished sleep efficiency. [6][7][8] Characterizing sleep patterns in older adults is important because sleep is important for good health.…”
Section: Introductionmentioning
confidence: 99%
“…CS reported the most sleep difficulties, FS reported improved sleep patterns, and NS reported the best sleep patterns. In assessing these sleep patterns, we were not able to utilize objective sleep data; however, we were able to collect subjective data, which plays a vital role in the assessment and diagnosis of insomnia (McCrae et al, 2005). Finally, we were able to measure these variables in a large, nationally representative sample of the USA.…”
Section: Psychology Health and Medicine 415mentioning
confidence: 99%
“…Differences between self-reported sleep and actual sleep time may also vary by health and sociodemographic factors (Lauderdale et al, 2008). However, it is important to emphasize that self-report data on sleep provide information that is used in assessment and diagnosis of sleep disorders such as insomnia (McCrae et al, 2005). Although there may be the presence of self-report bias, lower sleep duration was observed among smokers than nonsmokers even after controlling for most demographic factors.…”
Section: Psychology Health and Medicine 415mentioning
confidence: 99%